GOOD CORPORATE GOVERNANCE, DEVIDEND, LEVERAGE AND FIRM VALUE - Kartikasari, Evi Dwi; Hermantono, Agung; Mahmudah, Annita (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2019)
The establishment of the company in carrying out its business generally for the survival of the company. The survival of the company  be achieved if the company's performance is good, it always increases and has good corporate governance. The value of the company is a reflection of the addition of the company's equity with the company's debt. type of research is descriptive quantitative. The sample of 32 companies included in publicly listed manufacturing companies using purposive sampling method. The results showed that good corporate governance which was proxy by institutional ownership and managerial ownership had no effect on Value of the firm. Devidend pay out ratio, leverage that is proxy by debt to assets ratio and debt to equity ratio, financial performance which is proxy by return on assets and return on equity has a significant effect on value of the firm.Keywords:Financial Performance, Good corporate governance, Devidend pay out ratio, Leverage, Value of the Firm.* Departement of Accounting, Sekolah Tinggi Ilmu Ekonomi KH Ahmad Dahlan, Jl. KH. Ahmad Dahlan No.41, Tlogoanyar, Kec. Lamongan, Kabupaten Lamongan, Jawa Timur 62115, Indonesia. https://doi.org/10.21632/irjbs.12.3.301-311